IDNLearn.com helps you find the answers you need quickly and efficiently. Ask your questions and receive prompt, detailed answers from our experienced and knowledgeable community members.
Sagot :
[tex]\text{Given that,}\\\\(x_1,y_1) = (-2,-3), ~~\text{and slope,}~~m = \dfrac 52\\\\\\\text{Now,}\\\\y -y_1 =m(x-x_1)\\\\\implies y +3 = \dfrac52 (x+2)\\\\\implies y = \dfrac 52(x+2) -3\\\\\\\implies y = \dfrac{5}2 x + 5 -3 \\\\\\\implies y = \dfrac 52 x + 2\\\\\\\text{This is the slope-intercept form(y =mx+b)}.[/tex]
Answer:
y+3=5/2(x+2)
Step-by-step explanation:
The image below shows my work but i hope this helps
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Thank you for choosing IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more solutions.